The International Heat Stress Genotype Experiment for modeling wheat response to heat: field experiments and AgMIP-Wheat multi-model simulations - Martre, Pierre; Reynolds, Matthew P.; Asseng, Senthold; Ewert, Frank; Alderman, Phillip D.; Cammarano, Davide; Maiorano, Andrea; Ruane, Alexander C.; Aggarwal, Pramod K.; Anothai, Jakarat; Basso, Bruno; Biernath, Christian; et al. (My University, 2017)
The data set contains a portion of the International Heat Stress Genotype Experiment (IHSGE) data used in the AgMIP-Wheat project to analyze the uncertainty of 30 wheat crop models and quantify the impact of heat on global wheat yield productivity. It includes two spring wheat cultivars grown during two consecutive winter cropping cycles at hot, irrigated, and low latitude sites in Mexico (Ciudad Obregon and Tlaltizapan), Egypt (Aswan), India (Dharwar), the Sudan (Wad Medani), and Bangladesh (Dinajpur). Experiments in Mexico included normal (November-December) and late (January-March) sowing dates. Data include local daily weather data, soil characteristics and initial soil conditions, crop measurements (anthesis and maturity dates, anthesis and final total above ground biomass, final grain yields and yields components), and cultivar information. Simulations include both daily in-season and end-of-season results from 30 wheat models.
Keywords: field experimental data; wheat; field experimentation; heat stress; simulation